2014
DOI: 10.1186/1756-3305-7-307
|View full text |Cite
|
Sign up to set email alerts
|

Innovative tools for assessing risks for severe adverse events in areas of overlapping Loa loa and other filarial distributions: the application of micro-stratification mapping

Abstract: BackgroundThe wide distribution of Loa loa infection (loiasis) throughout the Democratic Republic of Congo (DRC) is a major obstacle to the plans to eliminate onchocerciasis and lymphatic filariasis (LF) because the standard drug regime is dependent on ivermectin, which cannot be used in co-endemic areas due to the risk of severe adverse events (SAEs). A better understanding of the micro-epidemiology, overlapping low and high risk areas, and how they relate to SAEs is critical to ensure safe and effective trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 16 publications
(21 reference statements)
0
41
0
Order By: Relevance
“…Furthermore, the presence of purine-nucleoside phosphorylase (EC 2.4.2.1)—enabling the conversions of guanine and adenine to deoxyguanosine and deoxyadenosine, respectively—ensures O. volvulus is robust to the deletion of ribonucleoside-diphosphate reductase (EC 1.17.4.1). Given the strikingly different pathways involved in the production of purines for the two species, any reliance by O. volvulus on this alternative pathway could be exploited to selectively target O. volvulus 7 , a credible prospect because inhibitors of purine-nucleoside phosphorylase already exist 38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the presence of purine-nucleoside phosphorylase (EC 2.4.2.1)—enabling the conversions of guanine and adenine to deoxyguanosine and deoxyadenosine, respectively—ensures O. volvulus is robust to the deletion of ribonucleoside-diphosphate reductase (EC 1.17.4.1). Given the strikingly different pathways involved in the production of purines for the two species, any reliance by O. volvulus on this alternative pathway could be exploited to selectively target O. volvulus 7 , a credible prospect because inhibitors of purine-nucleoside phosphorylase already exist 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Ivermectin is solely microfilaricidal, which means it must be given over decades, past the lifespan of the long-lived adult worms 5,6 . Moreover, in much of Central Africa where Loa loa is co-endemic with O. volvulus , ivermectin cannot be used due to the risk of Loa -associated irreversible neurological severe adverse events and death 7 . Despite its success in Latin America and small foci in Africa, elimination of onchocerciasis in Africa is unlikely to be achieved within the proposed timeframes solely through MDA with ivermectin 8 .…”
mentioning
confidence: 99%
“…Given the often high levels of co[ 2 8 8 _ T D $ D I F F ] -infection with onchocerciasis that exist in populations [79,90], the significant number of people with onchocerciasis who have already received ivermectin, and the commitment to ensure those still infected with O. volvulus receive the necessary treatment [91], it is likely that many individuals currently infected with L. loa will receive, or have already received, ivermectin. Is there a subset of the human population who is genuinely amicrofilaraemic, or is this observation due to the limited sensitivity of the currently available microscopy-based diagnostics?…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Recent studies on SAEs in Bas Congo, DRC [ 48 ], have shown that the events are associated with areas considered to be at lower risk with a RAPLOA prevalence of between 20-40%, but were found to be 10–16 times higher than elsewhere. This implies that the RAPLOA estimated prevalence is not necessarily the primary indicator of SAE risk, but rather the intensity of infection in individuals when they have high parasitaemias of L. loa (≄30,000 mf/ml) [ 49 ].…”
Section: Diversity Of Settings Epidemiology and Interventionsmentioning
confidence: 99%